Wisdom Tooth Formation as a Method of Estimating Age in a New Zealand Population - Annabelle McGettigan; Kimberley Timmins; Peter Herbison; Helen Liversidge; Jules Kieser (Dental Anthropology Association, 2011)
Dental ageing relies on assumptions about the progression of tooth development from the middle trimester to adulthood and relative stability of this process in the face of adverse dietary, hormonal, disease or nutritional factors. Most studies of dental ageing employ the method of Demirjian et al., (1973), which is based upon an assessment of crown and root formation stages from dental radiographs. Unfortunately, this method has a ceiling effect at age 16, when the second molar attains full maturity. The aim of our study was to extend the window of ageing by using the development of the third molar teeth. Panoramic radiographs of 207 (105 males) children aged between 7 years, 6 months and 18 years formed the basis of this study. Upper and lower left wisdom teeth were scored according to Demirjian et al. (1973) by a single examiner. Intra-examiner reliability was evaluated by repeat scoring of a randomly selected (10%) sample one week after the initial staging. These showed a consistency of 76% for the mandibular data and 95% for the maxillary data, giving an overall percentage of 85%. When the re-scored teeth were not consistent with their original score, this differed only by one stage. In this population males were advanced in their third molar development and this trend was more marked for maxillary than mandibular wisdom teeth. Hence, the New Zealand population examined, males were more advanced in their third molar development and this trend was more marked for maxillary than mandibular teeth.